Enhancing Micro-CT methods to quantify oil content and porosity in starch-gluten matrices. (November 2018) - Contardo, Ingrid; Bouchon, Pedro
Abstract: X-ray micro-computed tomography (micro-CT) is a non-destructive method to study internal structures based on the differences in the strength of x-ray attenuation within a scanned material. In the field of food science, distinguishing certain components represents a challenge as food ingredients have low x-ray attenuation. The objective of this study was to explore the potential application of different agents to enhance x-ray attenuation in fried starch-gluten products, quantify oil content and air porosity, and analyze its microstructure using micro-CT. Control dough, dough stained with a Lugol solution (0.1% (w/w)) or with a BaCl2 solution (0.5% (w/w)), and samples fried in oil stained with Nile Red (0.05 g/L) or stained with Lugol solution and fried in Nile Red were examined. All agents studied improved x-ray attenuation in fried dough. Quantitative analysis of micro-CT images showed that samples attenuated with Nile Red exhibited the smaller standard deviation in oil content and air porosity. These results did not show significant differences with those determined by means of traditional analytical methods. Graphical abstract: Highlights: Fried starch-gluten products were successfully characterized using micro-CT. Lugol, Barium, and Nile Red agents improved X-ray attenuation. Oil and porosity were quantified using micro-CT image analysis. Results from image analysis were comparable to those obtained using analytical methods. Nile Red allowed the smallest standard deviation in oil and porosity determinations.